Interactions of arbuscular mycorrhizal fungi and spore-associated bacteria - Ridsdale, Carmen Jane (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
Arbuscular mycorrhizal (AM) fungi are naturally occurring in roots of terrestrial plants. AM fungi are capable of benefiting the host plant through various mechanisms such as enhanced nutrient supply, alleviation of environmental stress and inhibition of plant fungal pathogens. AM fungal spore-associated bacteria have been previously isolated and shown to have plant growthpromoting (PGP) abilities by several authors. Some bacterial isolates are able to promote AM fungal colonisation of host plants and are known to be mycorrhizal helper bacteria (MHB). This study focused on the isolation of AM fungal spore-associated bacteria, characterization of the isolates according to plant growth promoting abilities and evaluation of their potential to enhance plant growth and mycorrhizal colonisation. AM fungi were extracted from soils sampled from natural indigenous forest sources, raspberry (Rubus idaeus cv. Heritage) and strawberry (Fragaria ananassa) farms in South Africa and from a raspberry (Rubus idaeus cv. Autumn Bliss) plantation in Argentina. A total of 52 sporeassociated bacteria were isolated from the external and internal surfaces of AM fungal spore morphotypes from the two countries. The bacterial isolates were evaluated for their PGP abilities such as phosphate solubilisation, indole-3-acetic acid production, ammonia production and inhibition of the fungal pathogens Fusarium oxysporum and Phythophthora nicotianae through mechanisms such as siderophore and/ or hydrolytic enzyme production. A total of 23 bacterial isolates from both South Africa and Argentina showing the most potential to be PGP, were identified molecularly as belonging to the genera Acinetobacter, Alcaligenes, Bacillus, Microbacterium, Micrococcus, Serratia and Staphylococcus. The ability of ten selected bacterial isolates showing multiple PGP capacity were evaluated for their plant growth promotion and mycorrhizal colonisation enhancement ability on raspberry (Rubus idaeus cv. Meeker). Significant differences in increased shoot and root dry weights were shown by the treatments compared to the uninoculated control. The highest increase in shoot and root dry weights were shown by South African (Bacillus mycoides) and Argentinean (Alcaligenes faecalis) isolates. AM fungal colonisation was significantly enhanced by the South African (Bacillus mycoides) and Argentinean (Micrococcus luteus) isolates compared to the AM fungal singly inoculated control.
Keywords: Mycorrhizal fungi; Host plants; Bacteria